Delayed onset of electromyographic activity of the vastus medialis relative to the vastus lateralis may be related to physical activity levels in females with patellofemoral pain - Briani, Ronaldo Valdir [UNESP]; de Oliveira Silva, Danilo [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Ferreira, Amanda Schenatto [UNESP]; Ferrari, Deisi; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2016)
The aims of this study were to examine group differences in muscle activation onset of the vastus medialis (VM) in relation to the vastus lateralis (VL) and pain level during stair ascent in females with patellofemoral pain (PFP) who maintain high and moderate levels of physical activity; to determine the association between physical activity level and muscle activation onset. Forty-three females with PFP and thirty-eight pain-free females were recruited and divided into four groups based on their level of physical activity: females with PFP (n = 26) and pain-free females (n = 26) who practiced a moderate level of physical activity and females with PFP (n = 17) and pain-free females (n = 12) who practiced an intense amount of physical activity. Participants were asked to ascend a seven-step staircase and the VM and VL activation onset was determined. Females with PFP who practiced high level of physical activity demonstrated delayed onset of VM (4.06 ms) compared to healthy females (-14.4 ms). Conversely, females with PFP who practiced moderate level of physical activity did not present VM delay (-2.48 ms) in comparison to healthy females (-9.89 ms). Furthermore, physical activity significantly correlated to the muscle activation onset difference (p = 0.005; R = 0.60). These findings may explain why controversial results regarding VM and VL muscle activation onset have been found.
Keywords: Knee pain; Muscle activity; Onset; Quadriceps